2017
DOI: 10.1038/ncomms15664
|View full text |Cite
|
Sign up to set email alerts
|

The microprotein Minion controls cell fusion and muscle formation

Abstract: Although recent evidence has pointed to the existence of small open reading frame (smORF)-encoded microproteins in mammals, their function remains to be determined. Skeletal muscle development requires fusion of mononuclear progenitors to form multinucleated myotubes, a critical but poorly understood process. Here we report the identification of Minion (microprotein inducer of fusion), a smORF encoding an essential skeletal muscle specific microprotein. Myogenic progenitors lacking Minion differentiate normall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
149
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(152 citation statements)
references
References 37 publications
3
149
0
Order By: Relevance
“…Myoblasts isolated from dysferlinopathy patients or derived from dysferlin-deficient mice proliferated with the normal rate [117,118], but showed decreased fusion efficiency in vitro as a result of activated signaling of the pro-inflammatory network inhibiting myogenesis [118]. In this context it is important to mention that dysferlin has been found in a protein complex with minion/myomerger, a fusogenic protein, which together with myomaker conveys the ability to form syncytia to myogenic and non-myogenic cells [119].…”
Section: Dysferlin In the Differentiation Growth And Regeneration Ofmentioning
confidence: 99%
“…Myoblasts isolated from dysferlinopathy patients or derived from dysferlin-deficient mice proliferated with the normal rate [117,118], but showed decreased fusion efficiency in vitro as a result of activated signaling of the pro-inflammatory network inhibiting myogenesis [118]. In this context it is important to mention that dysferlin has been found in a protein complex with minion/myomerger, a fusogenic protein, which together with myomaker conveys the ability to form syncytia to myogenic and non-myogenic cells [119].…”
Section: Dysferlin In the Differentiation Growth And Regeneration Ofmentioning
confidence: 99%
“…While syncytins are captured virus fusogens in trophoblasts (Blond et al, 2000;Huppertz and Borges, 2008;Mi et al, 2000), Eff-1 and its paralog Aff-1 in C. elegans epithelial and vulval cells, respectively (Mohler et al, 2002;Sapir et al, 2007), and HAP2 (also known as GCS1) in protist and plant gametes (Liu et al, 2008;Pinello et al, 2017;Valansi et al, 2017) resemble type II viral fusogens (Pérez-Vargas et al, 2014;Fédry et al, 2017). Interestingly, vertebrate myoblast fusion utilizes a bipartite fusogen comprising a seven-pass transmembrane protein myomaker (Millay et al, 2013), and a micropeptide myomixer (also known as myomerger or minion) (Bi et al, 2017;Quinn et al, 2017;Zhang et al, 2017). These two proteins work independently to control distinct steps of membrane remodeling during myoblast fusion, with myomaker involved in membrane hemifusion and myomixer in generating the membrane stress necessary for fusion pore formation (Leikina et al, 2018).…”
Section: The Attacking Cell: Fusion-competent Myoblastmentioning
confidence: 99%
“…Functional inferences can also be drawn from microprotein sequence conservation (Fig. 4d-f), as several characterized smORFs have excellent conservation by PhyloCSF and BLAST 1317 . Having identified thousands of smORFs, additional biological data can easily be mined to elucidate their roles.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several mammalian microproteins have been characterized with fundamental roles in cell biology ranging from DNA repair 13 , mitochondrial function 14,15 , and RNA regulation 16 . In addition, microproteins that regulate physiological processes including muscle development 17 , muscle function 18,19 , and metabolism 20 have been discovered. Together these studies demonstrated that genomes contain many functional smORFs and renewed interest in annotating all protein-coding smORFs.…”
mentioning
confidence: 99%